PENGARUH DURASI IRIGASI TETES TERHADAP REDUKSI LENGAS TANAH PADA LAHAN POLYBAG - I DEWA GEDE JAYA NEGARA; SALEHUDIN SALEHUDIN; I WAYAN YASA; HERI SULISTIYONO; ANID SUPRIYADI; LALU DWIKI AXELA ANDRIAWAN (GANEC SWARA, 2023)
Soil moisture is an important factor needed by plants for growth, and therefore the amount of soil moisture that can be stored depends on the type of soil or the composition of the soil-forming materials. Compost is one of the nutrients that is often used in the manufacture of planting media on land in the form of polybags, and the amount of compost composition on the soil is thought to greatly affect the ability to store water in the media, both the size and duration of storage. This study aims to examine the effect of using compost on storage of irrigation water in the form of soil moisture and how long it can be stored. in three-storey drip irrigation. The main data analyzed is soil moisture data (w) and the results of the analysis and discussion and conclusions are drawn descriptively. The results of the analysis show that the initial soil moisture content in the range of 19% -25%, can be given additional soil moisture by irrigation of about 12%. The average daily decrease in soil moisture that occurs in soil variation 1 (70%: 30% ) is 3% -4.4% and in soil variation 2 (50%: 50%), the average moisture reduction is around 3% -6%, soil moisture reduction in variation 2 is greater than soil variation 1 for all floors.